Serum Uric Acid, Alanine Aminotransferase, Hemoglobin and Red Blood Cell Count Levels in Pseudoexfoliation Syndrome - Hüseyin Simavlı; Yasin Yücel Bucak; Mehmet Tosun; Mesut Erdurmuş (Journal of Ophthalmology)
Purpose. The pathogenesis of pseudoexfoliation (PEX), the most common cause of secondary glaucoma, has not been clearly identified, but there is increasing evidence that points out the role of oxidative stress. The aim of this study is to evaluate some of the most commonly used blood parameters, hemoglobin (Hb), red blood cell count (RBC), alanine aminotransferase (ALT), and uric acid (UA) levels, in subjects with PEX. Materials and Methods. This study is performed in a state hospital between November 2011 and December 2012. Retrospective chart review of subjects who underwent cataract surgery was performed. Thirty-one healthy subjects with PEX and 34 healthy subjects without PEX were evaluated. Hb, RBC, ALT, and UA levels were recorded. Student’s t-test was used to compare the two groups. Results. The mean age was 73.6±14.1 years in PEX group and 70.1±12.7 in control group p=0.293. Hb, RBC, ALT, and UA levels did not show a statistically significant difference among PEX and control groups (p>0.05 for all). Conclusion. Serum levels of Hb, RBC, ALT, and UA levels were similar in subjects with and without PEX. Further studies are needed to clarify the precise role of Hb, RBC, ALT, and UA in the pathogenesis of PEX.